MEDIA PEMBELAJARAN MENGENAL HEWAN LAUT MENGGUNAKAN KARTU RFID DI TK PERTIWI III WONOREJO CEPU KABUPATEN BLORA PROPINSI JAWA TENGAH - Wibowo, Lastoni; Wahyusari, Retno; Herraprastanti, Eva Hertnacahyani; Gunawan, Helmi; ., Suprawikno; Korawan, Agus Dwi; Ghifari, Muhammad Al; Salsabilla, Dea; Indriyatni, Lies; Kurniawati, Endang (STIE Pelita Nusantara, 2023)
Learning activities in the Study Group (KB) are fun and do not burden children, so teachers are required to develop learning media. The problems faced by partners are that partners do not yet have learning media to get to know marine animals and the need for training in the use of learning media for partners. Based on an analysis of the situation and conditions faced by partners, the solution offered is to create and train for the use of learning media to get to know marine animals using an RFID card. This community service activity was carried out by a team from STT Ronggolawe Cepu in collaboration with a team of servants from STIE Pelita Nusantara Cepu. The conclusion of this activity is the creation of learning media to get to know marine animals using an RFID card and partners get learning media to get to know marine animals so that teachers can more easily introduce marine animals to students. Partners also gain knowledge and can apply technology through learning media about marine animals that have been created.